Stevens' Handbook of Experimental Psychology and Cognitive Neuroscience 2018
DOI: 10.1002/9781119170174.epcn106
|View full text |Cite
|
Sign up to set email alerts
|

Education and Memory

Abstract: How can psychology research be used to improve education? In this chapter we review empirical research on learning and memory that has the potential to enhance classroom education. First we identify several basic principles of memory. Then we explore seven tools for enhancing learning: spaced practice, interleaving, retrieval practice, elaborative interrogation, self‐explanation, mnemonics, and self‐regulated learning. In reviewing each strategy we highlight laboratory research and research conducted in repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 193 publications
0
5
0
2
Order By: Relevance
“…A wealth of empirical research in laboratories and classrooms over the last 20 years has clearly demonstrated that not all study strategies are equally effective (for reviews see [ 5 – 7 ]). On one hand, retrieval practice and spaced studying are two highly effective study strategies that help learners of all ages and abilities to build robust, flexible, and long-lasting knowledge in many domains [ 5 , 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A wealth of empirical research in laboratories and classrooms over the last 20 years has clearly demonstrated that not all study strategies are equally effective (for reviews see [ 5 – 7 ]). On one hand, retrieval practice and spaced studying are two highly effective study strategies that help learners of all ages and abilities to build robust, flexible, and long-lasting knowledge in many domains [ 5 , 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 Studies in cognitive and educational psychology provide evidence of how higher education students should approach their study to improve learning and retention to maximise their academic results 2 and improve their education. 3 Therefore, making students learn is an essential part of teaching, as in this way, students can be helped to increase their understanding and achievements. 4 However, specific study techniques that are known to be better than others are not always taught or applied in education, 2,5 including in dental education.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare students need to learn large amounts of information for their examinations, which can be difficult for those who do not use evidence‐based study strategies 1 . Studies in cognitive and educational psychology provide evidence of how higher education students should approach their study to improve learning and retention to maximise their academic results 2 and improve their education 3 . Therefore, making students learn is an essential part of teaching, as in this way, students can be helped to increase their understanding and achievements 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, self-regulated learning aims at formative evaluating and optimizing one's own learning process in a strategy-based and goal-oriented manner. For this, learners must be aware of what they already know, what they still have to learn, and how they can best achieve their learning goal [23,30].…”
Section: Introductionmentioning
confidence: 99%